PERKECAMBAHAN BENIH PALA (Myristica fragrans Houtt.) DENGAN METODE SKARIFIKASI DAN PERENDAMAN ZPT ALAMI - Stya Dharma,Sakka Samudin, Adrianton, I Putu Eka (AGROTEKBIS, 2015)
This study was aimed to breaking down the nutmeg germination dormancy by two different methods. This research was conducted from July to september 2014 in Seed Science and Technology Laboratory, Faculty of Agriculture,Tadulako University. A Complete Randomized Design (CRD) was used with two treatments. The First factor was level of scarification namely without scarification, complete scarification with sand, scarification with fracturing. The second factor is immersion of natural plant growth regulator (PGPR) : Aquades, coconut water (100%). The study has 6 combinations of treatments. Each cobination was repeated three times. Threfore, it was consists of 18 experiment units, and each experiment unit used 20 seeds. Total seed used in this experiment was 360 nutmegs. The results showed treatment was significant improve e length of sprout radicle, plumula length and seedling dry weight. Immersed with natural PGPR immersion and the interaction with scarification was no correlation on the seedling.  Fully scarified seed is the best treatment, 96.66% of seeds were germinated, the rate of germination was 39.09%, and germination length was 25.78 days, radicle length was 12.35, plumula length was 17.27, and seedling dry weight was 3.71 g.